The Influence of Media as a Non-state Actor in International Relations – Syrian and Ukrainian refugees’ crisis- case study - Walaa Abdelrahman Fouda; Obaid A. Al Blooshi (Medaad)
In any country, the role of media is vital as it is a medium to keep the people informed on the latest developments in the country and elsewhere. Due to this assumed role of the press, media outlets are expected to remain objective, honest, and free from biases. Furthermore, media outlets were more localized traditionally. However, this media aspect has changed extensively in recent decades, most notably with the rise of the internet. Today, many prominent media outlets are either inclined toward a fixed political ideology or are owned by large media conglomerates with their corporate interests to look out for. This report aims to identify the role of media as a non-state actor in international relations. This is an important study to conduct in an era when media outlets are no longer limited to just their domestic market but instead have a truly global reach. Using a case study analysis method of data collection with a qualitative methodology, this study analyzes two prominent recent international events, the Syrian refugee crisis, and the Ukrainian refugee crisis. From the case study analysis, this study has established that the media now has the power of public diplomacy to influence policies in international relations as well.